Pendidikan Anak Usia Dini Di Era Society 5.0 - Elviona, Nola; Putri, Zakia Nabila; Aini, Sahara Usnul (Jurnal Family Education, 2023)
This article introduces the concept of Society 5.0, which emphasizes the integration of technologies, such as the internet of things, big data, and artificial intelligence, into children's daily lives. This education highlights the importance of preparing children to coexist with technology and harness its potential. Therefore, the important role of educators is very influential in facilitating the transition of early childhood education in the era of society 5.0. They are responsible for guiding and supporting children's learning in technology-filled environments. Emphasizing the need for innovative educational strategies that are in line with child development in the era of Society 5.0. These strategies include the integration of educational technology, project-based learning, skills development 4.0, active and collaborative learning, individualization of learning, lifelong learning, digital safety and ethics, and parental involvement. As well as discussing the various roles of educators and educational methods that can be applied in early childhood education, such as technology-based learning, Virtual Reality (VR) and Augmented Reality (AR)-based learning, game-based learning (Gamification), experience-based learning, AI-based artificial intelligence-based learning, collaboration-based teaching, digital skills education, project-based learning, and a focus on creativity and critical thinking campaigns. The end goal is to create quality human resources, foster independence, creativity, competitiveness, and a lifelong learning mindset in children.